2021
DOI: 10.1038/s41598-021-83288-9
|View full text |Cite
|
Sign up to set email alerts
|

The potential pathways underlying the association of propyl-paraben exposure with aeroallergen sensitization and EASI score using metabolomics analysis

Abstract: Propyl-paraben exposure is associated with aeroallergen sensitization, but its association with atopic dermatitis (AD) is inconclusive. No studies have been conducted on the metabolomic pathways underlying these associations. We investigated the associations between propyl-paraben exposure and aeroallergen sensitization, AD, and Eczema Area and Severity Index (EASI) score and identified the underlying pathways using untargeted metabolomics analysis. We enrolled 455 children in a general population study. Skin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 50 publications
1
13
0
Order By: Relevance
“…Taken together with the relationship between parabens, the effects of biocides [ 8 ], and allergies, the hygiene hypothesis is considered the most likely explanation for the relationship between atopic dermatitis and parabens, which are antimicrobial agents, resulting in the predominance of Th2. Since Lee et al [ 26 ] demonstrated that propylparaben exposure was associated with the Eczema Area and Severity Index (EASI score), partially via metabolomic changes related to oxidative stress, atopic dermatitis in the present study may have been induced by parabens through a different pathway to the predominance of Th2.…”
Section: Discussionmentioning
confidence: 55%
“…Taken together with the relationship between parabens, the effects of biocides [ 8 ], and allergies, the hygiene hypothesis is considered the most likely explanation for the relationship between atopic dermatitis and parabens, which are antimicrobial agents, resulting in the predominance of Th2. Since Lee et al [ 26 ] demonstrated that propylparaben exposure was associated with the Eczema Area and Severity Index (EASI score), partially via metabolomic changes related to oxidative stress, atopic dermatitis in the present study may have been induced by parabens through a different pathway to the predominance of Th2.…”
Section: Discussionmentioning
confidence: 55%
“…Urinary metabolomes have been shown to be significantly modulated by specific agent exposure in the setting of AD: propyl-paraben has recently been demonstrated to be associated with aeroallergen sensitization and EASI score, mainly through the induction of metabolomic changes in specific metabolic pathways involving oxidative-stress response, mTOR, peroxisome proliferator-activated receptors, aryl hydrocarbon receptor signaling, and tricarboxylic acid cycle [ 13 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a metabolomics analysis of skin tissues and biofluids has also been employed for the assessment of toxic and non-toxic external substance exposure. For example, Lee et al analyzed the association of propyl paraben exposure with aeroallergen sensitization using urine metabolomics [ 13 ], while our group evaluated metabolomic pattern variations in patients with actinic keratoses before and after field-cancerization therapy with ingenol mebutate [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to medications, parabens are widely used as preservatives in cosmetics, personal care products, and food [53]. In one study that involved 455 children, it was proved that exposure to propylparaben is related to aeroallergen sensitization and an increase of Eczema Area and Severity Index (EASI) score [52]. Several studies also confirm that parabens are significantly associated with allergic diseases development [54,55].…”
Section: Sweetenersmentioning
confidence: 99%
“…There is a range of data showing the association between parabens exposure and allergic sensitization [52]. In addition to medications, parabens are widely used as preservatives in cosmetics, personal care products, and food [53].…”
Section: Sweetenersmentioning
confidence: 99%